Nutritional, antinutritional and phenological characterization of promising forage species for animal feeding in a cold tropical zone - Ramos, Lesvy; Apráez, José Edmundo; Cortes, Kris Stephany; Apráez, José Julián (Revista de Ciencias Agrícolas, 2021)
The search for forages with high biomass production and high nutritional content has made it possible to find food alternatives that, due to their nutritional benefits and resistance to adverse environmental factors, are the best option for herbivores. With the knowledge of farmers, producers and the experience of researchers, 12 species most frequently used in animal feeding were selected, identified and classified in the University's PSO herbarium of the University of Nariño. These were phenologically, nutritionally and antinutritionally characterized. Of these species, four belonged to the Asteraceae family; the Fabaceae, Adoxaceae and Malvaceae families were represented by two species; the Salicaceae and Cucurbitaceae families were represented by one and were propagated in nursery. In the nutritional composition, the Retamo (Genista monspessulana) stood out for its high dry matter content with 34.2%. Unlike the Chauchilla (Cyclanthera brachystachya), with 8.79%, the Sauco (Sambucus peruviana) had a higher content of protein 25.93%, followed by Abutilon (Abutilon pictum) with 23.42%. Chauchilla (Cyclanthera brachystachya) had the highest crude fiber content, with 21.59%, NDF of 38.06%, and FDA 27.23%. Tannins were the most common secondary metabolites in the species evaluated with moderate or low levels; sterols were present at low levels, and saponins and alkaloids yielded negative values.